Optimal Locating for Physical Development of Sorkhankalate City, Using Analytic Hierarchy Process Method )AHP) - Ahmad PurAhmad; Fardin Ahmadzadeh; Masomeh Mahdian Bahnamiri; Ali Mahdi (جغرافیا و توسعه, 2014)
Today, one of the most important and complex issues for urban programmers and  decision making is locating  suitable places for future development of cities and determining suitable lands, which this objective will obtain  with a comprehensive  view on all the effective factors   on the physical urban development. To do this, the present research which is a developmental-applicable type, with the purpose of determining suitable locations for future  development  of Sorkhankalate city in Golestan province  has studied this issue by descriptive- analytical method. For this purpose, multi-criteria  evaluation method  based on Analyzing Hierarchical Process (AHP) in GIS environment is used, and during this period, 13 natural and anthropological criteria have been  used. The obtained results show that suitable developing lands with the area of 33.61 percent are mainly located in the south and southeast and southwest parts , and the  lands with low and very low suitability with an area of 38.42 percent are located in northern and northeastern and northwestern. With the application of proper strategies of development and leading residential and activity centers to suitable lands, it is possible to stop development of residential areas in unsuitable lands and use resources in better ways along side with preserving agricultural lands of the area. Finally, with the application of the algebraic relation, all agent plans were overlapped together with  GIS environment and the lands' potential plan of the areas in the limit of the Hadishahr  project of Sorkhankalate city was classified for city development. Finally, the basic suggestion of the present findings is concentrating on the future development of the city in the northern, northeastern, and northwestern, considering the suitable existing situation.